2022
DOI: 10.3389/fnut.2022.1018502
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fruit intake on functional constipation: A systematic review and meta-analysis of randomized and crossover studies

Abstract: Functional constipation (FC) is commonly treated with fruits whose efficacy remains unclear. We conducted a meta-analysis of fruit intervention for FC and provided evidence-based recommendations. We searched seven databases from inception to July 2022. All randomized and crossover studies on the effectiveness of fruits on FC were included. We conducted sensitivity and subgroup analysis. A total of 11 studies were included in this review. Four trials showed that kiwifruits have significantly increased stool fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 55 publications
0
0
0
Order By: Relevance
“…The lack of fiber is a forefront factor among the well-known risk factors of childhood constipation [57]. The association of fiber in food and constipation has been established by several studies [58][59][60][61][62]. Dietary fibers are a non-digestible form (resistant toward human intestinal enzyme) of composite saccharides, basically cellulose and noncellulosic polysaccharides, for example, hemicellulose, pectic constituents, mucilage, gums, and a noncarbohydrate ingredient lignin.…”
Section: Risk Factorsmentioning
confidence: 99%
“…The lack of fiber is a forefront factor among the well-known risk factors of childhood constipation [57]. The association of fiber in food and constipation has been established by several studies [58][59][60][61][62]. Dietary fibers are a non-digestible form (resistant toward human intestinal enzyme) of composite saccharides, basically cellulose and noncellulosic polysaccharides, for example, hemicellulose, pectic constituents, mucilage, gums, and a noncarbohydrate ingredient lignin.…”
Section: Risk Factorsmentioning
confidence: 99%
“…Moreover, three high-quality studies found that kiwifruits have a better effect on stool symptoms and consistency (assessed by the Bristol stool scale) than Ficus carica paste [MD = 0.39, 95% CI (0.11, 0.66), p < 0.05, I 2 = 27%]. Analyzing the prebiotic effects, five trials showed that fruits increased the amount of Lactobacillus acidophilus [MD = 0.82, 95% CI (0.25, 1.39), p < 0.05, I 2 = 52%], and that pome fruits, citrus fruits, and berries increased bifidobacteria more than stone fruits [MD = 0.51, 95% CI (0.23, 0.79), p < 0.05, I 2 = 84%] [55]. No similar data are currently available for children.…”
Section: Fibers In Constipationmentioning
confidence: 99%
“…2022 Oct 6;9:1018502 Objetivo. Evaluar el efecto del consumo de ciertas frutas en el tratamiento de la constipación funcional 10 .…”
Section: ) Gearry R Fukudo S Barbara G Et Al Consumption Of 2 Green K...unclassified
“…Por último, la revisión de Huo et al 10 incluyó ensayos aleatorizados paralelos y cruzados, con la particularidad de evaluar no solo el efecto del kiwi, sino también el de otras frutas. Sin embargo, tiene numerosas limitaciones que dificultan la interpretación de sus resultados.…”
Section: Conclusiones Y Recomendacionesunclassified
See 1 more Smart Citation